New frontiers in oncolytic viruses: optimizing and selecting for virus strains with improved efficacy - Lundstrom K (Dove Medical Press, 2018)
Kenneth Lundstrom PanTherapeutics, Lutry, Switzerland Abstract: Oncolytic viruses have demonstrated selective replication and killing of tumor cells. Different types of oncolytic viruses – adenoviruses, alphaviruses, herpes simplex viruses, Newcastle disease viruses, rhabdoviruses, Coxsackie viruses, and vaccinia viruses – have been applied as either naturally occurring or engineered vectors. Numerous studies in animal-tumor models have demonstrated substantial tumor regression and prolonged survival rates. Moreover, clinical trials have confirmed good safety profiles and therapeutic efficacy for oncolytic viruses. Most encouragingly, the first cancer gene-therapy drug – Gendicine, based on oncolytic adenovirus type 5 – was approved in China. Likewise, a second-generation oncolytic herpes simplex virus-based drug for the treatment of melanoma has been registered in the US and Europe as talimogene laherparepvec. Keywords: immunotherapy, viral vectors, clinical trials, drug approval